2008
DOI: 10.1111/j.1744-7909.2008.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Anthocyanins and Exploration of Relationship between Their Composition and Petal Coloration in Crape Myrtle (Lagerstroemia hybrid)

Abstract: Petal coloration and pigment components in 12 American crape myrtle cultivars (Lagerstroemia indicaxLagerstroemia fauriei) and five Chinese crape myrtle cultivars (L. indica hybrids) were studied. Color was measured by CIEL*a*b* scale and anthocyanin composition of crape myrtle was determined using high-performance liquid chromatography coupled to photodiode array detection and electrospray ionization mass spectrometry. The presence of the previously reported delphinidin 3-O-glucoside, petunidin 3-O-glucoside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Zhang et al (2008) reported that the red or purple flower color is probably the result of specific anthocyanin accumulation that was inherited from L. indica. White flower color is associated with L. fauriei.…”
Section: From 50mentioning
confidence: 99%
“…Zhang et al (2008) reported that the red or purple flower color is probably the result of specific anthocyanin accumulation that was inherited from L. indica. White flower color is associated with L. fauriei.…”
Section: From 50mentioning
confidence: 99%
“…, Zhang et al. ). Crape myrtle breeding is a long process, involving evaluation of many phenotypic traits in full‐grown plants.…”
mentioning
confidence: 99%
“…Hz, H-6) and 9.28 (s, H-3), 9.34 (s, H-7'), 9.56 (s, H-4') and 10.7 (s, H-5). 13 C NMR in broad band de-coupled DMSO-d 6 as solvent in 100 MHz gave peaks at δ: 93.3 (C-6), 98.1 (C-3), 103.0 (C-8), 115.0 (C-10), 115.6 (C-3'), 119.9 (C-6'), 121.9 (C-5'), 135.7 (C-2'), 145.0 (C-1') 146.8 (C-9), 156.1 (C-7), 160.7 (C-5), 163.8 (C-2) and 175.8 (C-4). Further mass spectrum in positive mode gave the peak at 271 (M+1) suggesting the molecular weight to be 270 m/z, which was found to match with molecular formula C-6'), 98.6 (C-1') and 93.7 (C-2').…”
Section: Spectral and Physical Data Of The Isolated Compoundsmentioning
confidence: 97%
“…12 The color components from the petals of L. indica have been recently identified as mainly flavones and flavonols using HPLC coupled with electrospray ionization mass spectrometry. 13 Since there are no other reports available on the isolation and characterization of colour components from the fruits, the present investigation was taken up to isolate and characterize the colour components from abundantly available fruits of L. indica which are generally considered a bio waste. The study also intended to investigate the dyeing and kinetic aspects of the colorant on silk.…”
Section: Introductionmentioning
confidence: 99%